Pengaruh Non Performing Loan (NPL) dan Biaya Operasional Terhadap Pendapatan Operasional (BOPO) Terhadap Harga Saham Pada PT. Bank Kb Bukopin, Tbk - C. W, Dian Purwati; Huda, Nurul; Juwani, Juwani (Universitas Serambi Mekkah, 2024)
This research aims to determine the effect of Non-Performing Loans (NPL) and Operational Costs on Operating Income (BOPO) on Share Prices at PT. Bank KB Bukopin, Tbk. This type of associative research uses primary data in and sourced from the research instrument, a list of tables containing data on total non-performing loans, total credit, operational costs, operating income and share prices at PT. Bank KB Bukopin, Tbk for 10 years, namely from 2013 to 2022. The population in this research is all financial reports of PT. Bank KB Bukopin, Tbk has been listed on the IDX from 2006 to 2022, which is 16 years. The sample in this research is the financial report of PT. Bank KB Bukopin, Tbk for 10 years, namely from 2013 to 2022. The sampling technique used in this research was purposive sampling. Documentation and literature study are data collection methods. The data that has been collected will be analyzed using the classical assumption test, multiple linear regression, multiple correlation coefficient, determination test, t test and f test. The research results show that Non-Performing Loans (NPL) and Operational Costs to Operating Income (BOPO) partially and simultaneously have a significant effect on the share price at PT. Bank KB Bukopin, Tbk.